Optimization of hand sanitizer gels containing soursop (Annona muricata L.) leaf extract using simplex lattice design method - Kosasih, Kosasih; Lismawati, Dita; Adinugroho, Rifael Satrio (Faculty of Pharmacy, Universitas Pancasila, 2025)
Soursop (Annona muricata L.) is a plant whose leaf extract contains alkaloids, flavonoids, saponins, and tannins and can be antibacterial. Based on the compounds it contains, soursop leaf extract can be an active substance in hand sanitizer gel preparations. This study aims to determine the characteristics of the resulting hand sanitizer gel and the optimum concentration of the base combination that can produce a qualified hand sanitizer gel. This study used a Simplex Lattice Design experimental method with two factors (carbomer 940 and HPMC). Three hand sanitizer gels were prepared, with a ratio of carbomer 940: HPMC for F1 (1%:0%), F2 (0.5%:0.5%), and F3 (0%:1%). Tests conducted on hand sanitizer gel preparations included organoleptic, homogeneity, spreadability, adhesion, pH, and viscosity. The results of physical properties tests (spreadability, adhesion, and viscosity) were analyzed using Design Expert 11. The results showed that carbomer 940 and HPMC could increase viscosity and adhesion but could decrease spreadability. Ethanol extract of soursop leaves (Annona muricata L.) could be formulated and optimized into hand sanitizer gels. The optimum formula contained carbomer 940 0% and HPMC 1%, obtained in Formula 3 with a desirability value of 0.986.